‘I speak slang, but wiv the teacher ‘normal’’. Language ideology in the primary classroom - Giuliana Ferri (Problemy Wczesnej Edukacji)
The paper is a work in progress investigating the perceptions of Standard English expressed by a group of children in their last year of primary school in a multicultural and multilingual educational setting in London. The theoretical framework employed to interpret the data, a series of group interviews with small groups, is that of language ideology. The idea brought forward in the paper is that language ideology is a habitus (Bourdieu, 1991) which attaches certain values to the prestige variety of a language, while devaluing non-standard varieties. Through the adoption of this theoretical lens, the paper attempts to evaluate the educational implications of this ideology.